Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja karyawan Dengan Kepuasan Kerja Sebagai variabel Intervenig Pada PT. Gama Agro Sejati Semarang - , Dwi Sri Wulandari; Sukirman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Abstract: The objectives of this study are: 1). To analyze the influence of organizational culture on employee job satisfaction. 2). To analyze the influence of motivation on employee job satisfaction. 3). To analyze the influence of organizational culture on employee performance. 4). To analyze the influence of motivation on employee performance. 5). To analyze the influence of job satisfaction on employee performance. 6). To analyze the influence of organizational culture on employee performance through job satisfaction. 7). To analyze the influence of motivation on employee performance through job satisfaction. This study uses a quantitative approach with the population consisting of all employees of PT. Gama Agro Sejati Semarang. The sampling technique used is saturated sampling, with a total of 71 respondents. Data were analyzed using an inferential approach through Smart-PLS 4.0 software. The results of the study show that: 1). Organizational culture has a positive and significant effect on job satisfaction. 2). Motivation has a positive and significant effect on job satisfaction. 3). Organizational culture has a positive and significant effect on employee performance. 4). Motivation has a positive and significant effect on employee performance. 5). Job satisfaction has a positive and significant effect on employee performance. 6). Job satisfaction is able to mediate the influence of organizational culture on employee performance. 7). Job satisfaction is able to mediate the influence of motivation on employee performance. Keywords: Organizational Culture, Motivation, Job Satisfaction, and Employee Performance.